Implementation of Public Sector Accounting Systems and Standards in Improving Financial Transparency - Sonjaya, Yaya; Prasetianingrum, Septyana; Auliyah, Iriana; Labo, Irwan Adam (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to evaluate the implementation of public sector accounting systems and standards, such as SAP and IPSAS, to improve financial transparency and accountability. The research investigates the contextual and systemic factors that support or hinder the successful adoption of these frameworks and offers insights into how institutional readiness, digitalization, and stakeholder engagement influence reporting outcomes. Research Design and Methodology: A systematic literature review (SLR) approach was employed to synthesize findings from prior studies. Institutional theory served as the conceptual framework, emphasizing coercive, mimetic, and normative pressures affecting policy implementation. The review focused on identifying key trends, challenges, and comparative insights related to financial reporting in different jurisdictions. Findings and Discussion: The findings reveal that adopting international public sector accounting standards has enhanced transparency and fiscal accountability in regions with robust institutional support. However, significant challenges remain, including bureaucratic resistance, resource limitations, and a lack of public financial literacy. Digital reporting technologies like XBRL are crucial in accelerating financial disclosures but require adequate training and infrastructure. The discussion highlights disparities in reporting outcomes due to differences in institutional readiness and underscores the need for tailored approaches to address local governance constraints. Implications: The study provides practical and managerial recommendations, emphasizing the importance of continuous training, modernization of IT infrastructure, and enhanced public access to simplified financial reports. Collaboration with independent auditors and civil society organizations is also suggested to strengthen accountability mechanisms. Future research should explore empirical data and sector-specific factors to enhance the understanding of financial reporting reforms further.